Human Botfly: A Case Report and Overview of Differential Diagnosis - Mina Shenouda MD; Garrett Enten BS; Thanh Nguyen MD; Devanand Mangar MD; Enrico Camporesi MD (SAGE Publishing, 2018)
Dermatobia hominis , commonly known as the human botfly, is native to Tropical America. As such, cutaneous infestation by its developing larvae, or myiasis, is quite common in this region. The distinct dermatological presentation of D hominis myiasis allows for its early recognition and noninvasive treatment by locals. However, it can prove quite perplexing for those unfamiliar with the lesion's unique appearance. Common erroneous diagnoses include the following: folliculitis, benign dermatocyst, and embedded foreign body with localized infection. We present a patient who acquired D hominis while she was in Belize. In this report, we discuss the presentation, differential diagnosis, diagnostic tests, and therapeutic approaches of human botfly lesion to raise the awareness about human botfly.